2012
DOI: 10.1002/app.37785
|View full text |Cite
|
Sign up to set email alerts
|

Interfacially confined RAFT miniemulsion copolymerization of styrene and butadiene

Abstract: In this study, ammonolyzed poly(styrene-alt-maleic anhydride) terminated with dithioester group can be self-assembled into an amphiphilic macro-reversible addition-fragmentation chain transfer (RAFT) agent, and RAFT group will be located in the interface of oil and water. RAFT polymerization of styrene (S) and butadiene (B) will be confined in the interface. The main work is to study the effect of degree of aminolysis, reaction temperature, and ratio of S/B on the polymerization kinetics and living characters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…O ‐Alkylxanthates and N , N ‐dialkyldithiocarbamates generally provide only poor control. An approach common to most recent experiments in emulsion polymerization has been the use of some form of macroRAFT agent, rather than direct use of a low‐molecular‐weight RAFT agent, to control emulsion polymerization. This has taken the form of an amphiphilic macroRAFT agent, which additionally replaces the surfactant, or a polystyrene seed latex formed by RAFT miniemulsion polymerization . This observation with respect to preferred RAFT agents and the use of macroRAFT agents is common to RAFT emulsion polymerization in general and is rationalized in terms of the desirability of localizing all of the RAFT agent in the particle phase for good control. Polymerization temperatures for experiments in which effective control was observed are ≥65 °C (emulsion polymerization) or ≥90 °C (solution).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O ‐Alkylxanthates and N , N ‐dialkyldithiocarbamates generally provide only poor control. An approach common to most recent experiments in emulsion polymerization has been the use of some form of macroRAFT agent, rather than direct use of a low‐molecular‐weight RAFT agent, to control emulsion polymerization. This has taken the form of an amphiphilic macroRAFT agent, which additionally replaces the surfactant, or a polystyrene seed latex formed by RAFT miniemulsion polymerization . This observation with respect to preferred RAFT agents and the use of macroRAFT agents is common to RAFT emulsion polymerization in general and is rationalized in terms of the desirability of localizing all of the RAFT agent in the particle phase for good control. Polymerization temperatures for experiments in which effective control was observed are ≥65 °C (emulsion polymerization) or ≥90 °C (solution).…”
Section: Discussionmentioning
confidence: 99%
“…The Zhejiang University patents appear to cover experiments similar to those published by the respective authors in the open literature as mentioned above . One patent has progressed to a PCT application.…”
Section: Raft (Co)polymerization Of Butadiene In Emulsionmentioning
confidence: 99%
“…have also attempted to solve the problem of delayed migration of the RAFT agent to micelle particles by using a mini emulsion polymerization technique that features polymerization inside monomer droplets. Although the above technique allowed the synthesis of narrow‐MWD ESBR, its inherent limitations resulted in small molecular weight and required the use of high temperatures, which caused gel formation …”
Section: Introductionmentioning
confidence: 90%
“…However, recently, RAFT ESBR polymerization studies reported solving these kinds of problem, and Yu et al attempted to solve the problem of the slow diffusion rate of RAFT agents into micelle particles while using a mini emulsion polymerization technique [39]. In addition, Mun et al reported the results of polymerization of RAFT ESBR using DBTC as a RAFT agent, having a similar molecular weight as conventional ESBR, but with a narrower dispersity.…”
Section: Introductionmentioning
confidence: 99%